2015
DOI: 10.1002/ajhb.22817
|View full text |Cite
|
Sign up to set email alerts
|

BaAka women's health and subsistence practices in transitional conservation economies: Variation with age, household size, and food security

Abstract: Here, we identify older BaAka women, caring for their own children and grandchildren, as particularly vulnerable to economic changes and food insecurity. We found older women, especially those in a community with greater restrictions on access to forest resources to have more dependents, reduced market integration, and low BMI relative to younger women in the population. Am. J. Hum. Biol. 28:453-460, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Though surprising, these results concord with work by anthropologists. Jost Robin-son and Remis (2016) found that among Aka women exposed to market integration and hunting restrictions, older women had lower body fat and increased inflammatory markers. Riddell (2013) found that within villages exposed to commercial forestry and conservation activities, Aka likelihoods changed more as compared to villages with less exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Though surprising, these results concord with work by anthropologists. Jost Robin-son and Remis (2016) found that among Aka women exposed to market integration and hunting restrictions, older women had lower body fat and increased inflammatory markers. Riddell (2013) found that within villages exposed to commercial forestry and conservation activities, Aka likelihoods changed more as compared to villages with less exposure.…”
Section: Introductionmentioning
confidence: 99%
“…There were just seven studies ( 39 , 46–48 , 61 , 64 , 69 ) that were regarded as utilising validated and gold-standard methodologies for measuring and reporting quantifiable contributions of wild, forest or NUS foods to diet quality. These studies utilised more than one dietary intake method (usually a combination of a quantified 24 h recall and a food frequency questionnaire) and repeat recalls on non-consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the involvement in intense activities might not relate to the overall energy spent over the day (Sarma et al, 2020), further study should explore gender differences in the energetic cost of food acquisition and preparation in relation with health among the Baka. As the Baka are currently experiencing nutritional transition (Reyes-García et al, 2019), and Baka women seem to play a key role as food providers, they might be more exposed to food insecurity, especially the older and post-reproductive women, as seen among the Aka (Robinson and Remis, 2016).…”
Section: Food Acquisition Activities In a Mixed Subsistence Societymentioning
confidence: 99%